GAMBARAN KONDISI KUALITAS AIR UNTUK RENCANA PENGEMBANGAN BUDIDAYA TAMBAK UDANG VANAME (Litopenaeus vannamei) DI PESISIR DESA TOENEKE KABUPATEN TIMOR TENGAH SELATAN - Susanti, Vinsensia Mariana; Liufeto, Franchy Ch (Nusa Cendana University, 2025)
Vaname shrimp farming (Litopenaeus vannamei) became one of the alternative fisheries production that is growing rapidly in this region, because promising prospects and profits. The purpose of this study was to determine description of water quality conditions required for the development of vaname shrimp (Litopenaeus vannamei) aquaculture in coastal Toineke Village, South Central Timor District. This study was conducted in coastal waters South Central Timor District (TTS), Kualin District, in Toineke Village for two weeks. Based on the results of water quality research it can be concluded that location A has a pH value of 4.9, dissolved oxygen of 0.6 ppm, nitrate of 0.005 mg/l and location B pH value of 5.34, dissolved oxygen of 0.59 ppm, nitrate of 0.009 mg/l, water quality that has been measured at location A and location B indicates that both locations do not qualify as vaname shrimp farming sites. Based on the research results obtained there are several water quality parameters that do not meet the optimal threshold. Researchers suggest water quality management. Keywords: Vaname shrimp farming (Litopenaeus vannamei).